Water quality parameters in terminal part of Gorganroud river during 2009-2010 - S. D. Balaly (ՀՀ ԳԱԱ հրատ.)
The present study was designed to demonstrate the seasonal variations in physical-chemical parameters in a part of River Gorganroud water for a period of twelve months from April 2009 to March 2010. Water samples were collected on monthly basis and analyzed for estimation of dissolved oxygen, pH, temperature, BOD5, COD and electrical conductivity. These parameters were compared to water quality standards to indicate probable pollution in the river Gorganroud. The overall water quality of the study site remained within the safe limits throughout the study period. An attempt has been made to explain the effect of seasonal changes on physical-chemical characteristics in a part of river Gorganroud water. 2009թ. ապրիլ ամսից մինչև 2010թ.-ի մարտ ամիսը իրականացվել են Գորգանրուդ գետի գետաբերանի ջրի ֆիզիկա-քիմիական ցուցանիշների ուսումնասիրություններ: Ամսեկան կտրվածքով վերցվել են ջրի փորձանմուշներ և հաշվարկվել են լուծված թթվածինը, pH-ը, ջերմաստիճանը, ԹԿՊ5, ԹՔՊ, ջրի մակերևույթի էլեկտրահաղորդականությունը: Գորգանրուդ գետի գետաբերանի աղտոտվածությունը բացահայտելու նպատակով ֆիզիկա-քիմիական ցուցանիշները համադրվել են ջրի որակի նորմերի հետ: Ընդհանուր առմամբ գետի ուսումնասիրված հատվածում հիդրոքիմիական ցուցանիշները չեն գերազանցել թույլատրելի սահմանները: Փորձ է արված բացատրել սեզոնային փոփոխությունների ազդեցությունը Գորգանրուդ գետի ջրի ֆիզիկա-քիմիական ցուցանիշների բնույթի վրա: В период с с апреля 2009г. до марта 2010г проводились исследования химических параметров воды р. Горганруд. Ежемесячно проводился отбор проб воды и определение растворенного кислорода, pH, температуры, БПК5, ХПК, электропроводности. В целях выявления вероятного загрязнения р. Горганруд полученные физико-химические показатели были сопоставлены со стандартами качества воды. В целом в исследованной части реки гидрохимические показатели были в пределах допустимого. Сделана попытка объяснить влияние сезонных изменений на физико-химические показатели воды в исследованной части р. Горганруд.
Keywords: Biology; Biochemistry; Biophysics